2013
DOI: 10.1227/neu.0b013e318273a1a3
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Haptics for Neurosurgeons

Abstract: Robots are becoming increasingly relevant to neurosurgeons, extending a neurosurgeon's physical capabilities, improving navigation within the surgical landscape when combined with advanced imaging, and propelling the movement toward minimally invasive surgery. Most surgical robots, however, isolate surgeons from the full range of human senses during a procedure. This forces surgeons to rely on vision alone for guidance through the surgical corridor, which limits the capabilities of the system, requires signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The robot also has haptic abilities, 20 allowing it to be used as a supervisorycontrolled device as well as a shared-control device.…”
mentioning
confidence: 99%
“…The robot also has haptic abilities, 20 allowing it to be used as a supervisorycontrolled device as well as a shared-control device.…”
mentioning
confidence: 99%
“…One study found that junior residents reported the most benefit from simulation with cadavers, followed by physical models and then haptic/computerized simulators. [2342] However, PGY-1 residents reportedly are least likely to be included in cadaveric simulation curriculum. [41] Interestingly, senior residents reported the most benefit from the computerized simulators, followed by cadavers and then physical models.…”
Section: Methodsmentioning
confidence: 99%
“…Then the contact force has to be fed back to the surgeon through the interface used to guide the tool's insertion. [22] Moreover, haptic systems, in connection with virtual reality devices, can be a valuable tool for the training of surgeons [23] and also for the evaluation of the skills of the surgeon. [24] This is the robotic configuration adopted in the robotic system for neurosurgery (named DAANS) developed by our research group.…”
Section: The Robotized Radiological Treatmentmentioning
confidence: 99%